Identification Of Damage Levels Of Residents' Houses Due To Earthquake in Pasaman 2022 - Rafki Imani; Hengki Kurniawan; Deded Eka Sahputra (Civil Engineering Collaboration, 2022)
The earthquake that occurred in Pasaman on February 25, 2022, has caused considerable losses to local residents. Thousands of buildings have been damaged and collapsed due to the earthquake, especially houses of residents, which in the field investigations are caused mainly by a lack of knowledge in building these houses. This study aims to identify the level of damage to houses damaged by the earthquake in Nagari Malampah, Pasaman District, West Sumatera. This research method is carried out by direct observation and investigation of the research location, then identifying the level of damage to residents' houses, by taking 10 samples of affected residents' houses. Of the 10 houses, the percentage of damage will be grouped based on the level of Light Damage, Medium Damage, and Heavy Damage, with reference to the Technical Guidelines for the Director General of Human Settlements, SNI 1726-2019, and PU Guidelines. The results of this study indicate that the percentage of the level of damage to houses that are lightly damaged ranges from 7.1% - 26%, the level of moderate damage ranges from 32.5% - 36.09%, and the level of residential buildings that experience severe damage (total collapse) ranged from 50% - 100%.